Physiology and training of a World Champion paratriathlete - Mujika , I.; Orbañanos, J.; Salazar, H. (International Journal of Sports Physiology and Performance, 2015)
Paratriathlon will debut at the Rio 2016 Paralympic Games, but research documenting the physiological attributes and training practices of elite paratriathletes is lacking. This case study reports on the physiology and training of a long-distance world-champion male paratriathlete (below-the-knee amputee) over 19 mo. His body mass and skinfolds declined respectively by ~4 kg and 30% in 2 mo and remained relatively constant thereafter. His swim test velocity increased by 4.4% over 6 mo but declined back to baseline thereafter. His absolute and relative cycling maximal aerobic power improved progressively by 21.8% and 32.6%, respectively. His power output at the individual lactate threshold (ILT) improved by 39.5% and 51.6%, and his power output at the onset of blood lactate accumulation (OBLA), by 59.7% and 73.4%. His maximal running aerobic velocity improved by 12.8%, and his velocity at ILT and OBLA increased by 38.9% and 44.9%, respectively. Over 84 wk he performed 813 training sessions (248 swim, 229 bike, 216 run, 120 strength), ie, 10 ± 3 sessions/week (mean ± SD). Swim, bike, and run volumes were 709 km (8 ± 3 km/wk), 519 h (6 ± 4 h/wk), and 164 h (2 ± 1 h/wk), respectively. Training at intensities below ILT, between ILT and OBLA, and above OBLA for swim were 82% ± 3%, 14% ± 1%, 4.4% ± 0.4%; for bike, 91% ± 3%, 6.2% ± 0.5%, 3.3% ± 0.3%; and for run, 88% ± 1%, 8.0% ± 0.3%, 3.5% ± 0.1%. The training volume for each discipline was lower than previously reported for competitive able-bodied Olympic-distance triathletes. He won the long-distance world championship in 8 h 14 min 47 s, nearly 30 min faster than his nearest competitor.